Simultaneous Pretreatment Process on The Isolation of Cellulose Mycrocrystalline from Oil Palm empty Fruit Bunches - Yulianti Sampora; Yenni Apriliany Devy; Dewi Sondari; Athanasia Amanda Septevani (Reaktor, 2020)
This research was aimed to evaluate the isolation of cellulose derived from empty fruit bunches (EFB), especially to increase the purity of cellulose content by subsequent pretreatment process involving delignification using NaOH followed by bleaching process using hydrogen peroxide (H2O2). The result showed that the cellulose content of the raw EFB content at 37.6% ± 0.3 w/w increased to 89.2% ± 0.4 w/w after the simultaneous pretreatment process. Moreover, after the simultaneous of bleaching process using H2O2, the lignin content can be reduced up to 3.1% ± 0.1 w/w which similar to cellulose standard (2.7% ± w/w). The utilization of simultaneous pretreatment process can also reduce the hemicellulose content from 23.9% ± 0.3 w/w (raw EFB) to 7.7% ± 0.2 w/w even lower than the cellulose standard (13.1% w/w). FTIR spectrum showed that the peak absorption of cellulose increased significantly upon the simultaneous process of delignification-bleaching. Morphological changes of the raw EFB compared to pre-treated EFB as a note by SEM analysis showed the significant transformation from the larger size and tightly bundles of micro-fibril cellulose into smaller size and individually separated micro-fibrils. Further through the simultaneous process exhibited yield at 80-85%, high crystallinity (70-80%), and good thermal stability in terms of Tonset at about 230-290 °C. From these results, it can be concluded that the subsequent pretreatment process involving NaOH delignification and H2O2 bleaching processes more likely offer a high selectivity of cellulose microcrystalline from lignocellulosic biomass material by simultaneous reduction of the hemicellulose and lignin content without disrupting the structure of cellulose.Keywords: bleaching; cellulose; delignified; microcrystalline cellulose; oil palm empty fruit bunches